1999
DOI: 10.1097/00000539-199903000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Monitoring of Carbon Dioxide Tension After Cardiothoracic Surgery in Infants and Children

Abstract: We conclude that, with certain caveats in mind, including the need to correlate the transcutaneous CO2 with an initial arterial CO2 value, transcutaneous CO2 monitoring can be used to estimate arterial CO2 in most neonates and children after cardiothoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
0
28
3
Order By: Relevance
“…In the neonatal population, the correlation of the TC with arterial PCO 2 and PO 2 values is excellent given the thinner epidermis and the limited development of the stratum corneum in neonates compared to older infants and children. (Tobias and Meyer 1997b;Berkenbosch et al 2001;Tobias et al 1999;Sivan et al 1992). In two prospective comparisons involving PICU patients with respiratory failure requiring mechanical ventilation, TC-CO 2 was significantly closer to arterial PO 2 values than the simultaneously measured ET-CO 2 value (Tobias and Meyer 1997b;Berkenbosch et al 2001).…”
Section: Neonatal Applicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the neonatal population, the correlation of the TC with arterial PCO 2 and PO 2 values is excellent given the thinner epidermis and the limited development of the stratum corneum in neonates compared to older infants and children. (Tobias and Meyer 1997b;Berkenbosch et al 2001;Tobias et al 1999;Sivan et al 1992). In two prospective comparisons involving PICU patients with respiratory failure requiring mechanical ventilation, TC-CO 2 was significantly closer to arterial PO 2 values than the simultaneously measured ET-CO 2 value (Tobias and Meyer 1997b;Berkenbosch et al 2001).…”
Section: Neonatal Applicationsmentioning
confidence: 95%
“…In two prospective comparisons involving PICU patients with respiratory failure requiring mechanical ventilation, TC-CO 2 was significantly closer to arterial PO 2 values than the simultaneously measured ET-CO 2 value (Tobias and Meyer 1997b;Berkenbosch et al 2001). The efficacy of TC-CO 2 monitoring has also been demonstrated following cardiovascular surgery in infants and children with congenital heart disease (CHD) (Tobias et al 1999). In all of these studies, various physiologic factors including increased dead space ventilation, residual shunt from CHD, and ventilation-perfusion mismatch can be expected to lead to significant inaccuracies with ETCO 2 monitoring.…”
Section: Neonatal Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…We published our experience with transcutaneous CO 2 monitoring during respiratory failure and following cardiothoracic surgery in infants and children. 3,4 In addition to the obvious problems with P ET CO 2 monitoring during high frequency ventilation, other factors including ventilation-perfusion inequalities, sampling errors, and patient positioning can interfere with its accuracy. In infants and children with respiratory failure, we found that transcutaneous monitoring provided a better estimation of PaCO 2 .…”
Section: High Frequency Ventilationmentioning
confidence: 99%
“…Therefore, we do not recommend placing on the thorax in patients who have sternotomy because of theoretical risk of superficial infection of wound. Affected by poor perfusion, edema, use of drugs such as dopamine (≥10 μg/kg/min) or epinephrine[12,13].Decreased accuracy with ventilation-perfusion inequalities, shunt, or intrinsic lung disease. Less accurate with smaller tidal volumes (ie, neonates and infants).…”
mentioning
confidence: 99%